Energy sector in Ecuador for public lighting: Current status. (January 2022) - Galindo, Santiago Pulla; Borge-Diez, David; Icaza, Daniel
Abstract: This paper describes the energy sector related to public lighting systems in Ecuador. It presents, in an orderly and succinct manner, the legal framework that governs this service and its model which includes the following aspects: its current structure, energy supply policies, competencies, tariff and subsidy specifications, service policies, planning, system modernization and related environmental aspects centering on the evolution and new law of the electricity sector. Nowadays, 5.56% of the energy generated in Ecuador is destined to the public lighting service. In 2019, 1382.14 GWh were destined to public lighting. For the next ten years, according to the Electricity Master Plan, an increase of 534, 076 new points of light is foreseen. In the short term, there is no defined plan to replace the systems with sodium lights to LED technology lights that will allow not only to accomplish the state energy efficiency policies, but also to reduce the energy consumption. The legal framework and the exposed data allow the different stakeholders to make informed intervention decisions. Graphical abstract: Image 1 Highlights: Ecuador has a legal framework for the management of public lighting. Growth horizon of the lighting system for the year 2025 is 534, 076 luminaires. There is no plan to replace luminaires with LED technology. Currently the public lighting system consumes 5.6% of energy of the national total. The largest number of luminaires are installed in the city of Quito.